Порівняльний аналіз функціональності та безпеки протоколів сімейства FHRP - Піглюк, І. М. (ХНУРЕ, 2024)
This article provides a comparative analysis of the First Hop Redundancy Protocols (FHRP) Aimed at enhancing network reliability and service continuity, the research evaluates each protocol's strengths and weaknesses. However, it is important to understand the specifics of each protocol and consider the specific needs of the network when selecting and configuring them.
Keywords: протокол сімейства FHRP; функціональність протоколів